2018
DOI: 10.1146/annurev-biochem-062917-012448
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Cell Biology: A Focus on Lipids in Cell Division

Abstract: Cells depend on hugely diverse lipidomes for many functions. The actions and structural integrity of the plasma membrane and most organelles also critically depend on membranes and their lipid components. Despite the biological importance of lipids, our understanding of lipid engagement, especially the roles of lipid hydrophobic alkyl side chains, in key cellular processes is still developing. Emerging research has begun to dissect the importance of lipids in intricate events such as cell division. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 159 publications
2
60
0
Order By: Relevance
“…3f, g , these results further suggest that the dissociated lipid in the cristae would slowly pass the outer membrane and be released into the cytoplasm. Dramatic membrane rearrangements occur during cell division 4 , 21 , 22 , and the high spatiotemporal monitoring of lipid properties by SPOT can provide insights on how the lipid is regulated in cytokinesis.…”
Section: Resultsmentioning
confidence: 99%
“…3f, g , these results further suggest that the dissociated lipid in the cristae would slowly pass the outer membrane and be released into the cytoplasm. Dramatic membrane rearrangements occur during cell division 4 , 21 , 22 , and the high spatiotemporal monitoring of lipid properties by SPOT can provide insights on how the lipid is regulated in cytokinesis.…”
Section: Resultsmentioning
confidence: 99%
“…Lipids can serve as signaling molecules and key regulators in fundamental cellular processes such as cell death, [ 10,15 ] proliferation, [ 16 ] and senescence. [ 13,14 ] Previous studies have shown that changes in lipid metabolism occur during TIS.…”
Section: Resultsmentioning
confidence: 99%
“…Whether through their structural or signaling roles, regulation of lipids has been linked to a plethora of cellular programs and diseases. Recent reviews highlight that regulation of specific lipids is required for fundamental processes such as cellular division [ 22 ] and cell death [ 16 , 23 ]. These key roles require tight control of lipid biosynthesis and metabolism in order to maintain cellular homeostasis [ 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%